Perencanaan Fasilitas Pariwisata di Desa Wisata Kerta, Kecamatan Payangan,Kabupaten Gianyar,Bali - Suputra, I Putu Arnawa; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2019)
The tourism development has led to changes in land use, social and ecnomic aspects. As the new flagship sector of Kerta Tourism Village which is one of the village’s clans designated as a tourist village in accordaance with Gianyar Regent Decree Number 429/E-02/HK in 2017on Payangan District, Gianyar Regency. So in developing the potential that must be with the planning of tourism facilities match to the Tourism Village Kerta condition. The research study uses descriptive qualitative analysis method with data collection tehniques such as observation, interview, documentation and literature study. The technique of data analysists used are reduction data, presentation data, and conclusion/verification. The determining technique of informant are using tehnique of purposive sampling, this research is limited by using tourism destination life cycle theory, tourism planning concept, facility concept, tourism village, concept, and tourism product component. The result of the research is that Kerta Tourism Village is currently in the phase of involvement, of local communities in the development and planning of tourism facilities in Kerta Tourism Village. It can be seen from the existence of tourism facilities that are still not optimal such as communications, electricity, restaurant, roads, wantilan, parking area, heatlh facilities and bins. Keywords : Tourism Planning, Facilities, Tourism Products and Village Tours